Red Onion Paste as a Form of Local Wisdom in Traditional Medicine of the Malay Community in Kuala Tungkal, West Tanjung Jabung Regency - Rahma Annisa (DIVERSITAS HAYATI, 2025)
The practice of rubbing red onion is a form of local wisdom that is still maintained by the Malay community in Kuala Tungkal as a traditional method of treating minor ailments, especially in children. This study aims to describe the procedure of rubbing red onion, the reasons for its continuation, and the community's perception of its effectiveness. The study used a descriptive qualitative approach through in-depth interviews, participatory observation, and documentation of 30 informants selected purposively. The data were analyzed using thematic analysis to identify patterns of use and the structure of local knowledge related to the practice of rubbing. The results showed that red onions are generally crushed and rubbed on the stomach, chest, back, and soles of the feet, with or without traditional oil. This practice is considered effective in reducing complaints such as flatulence, colds, mild fever, and helping children relax and sleep better. Knowledge about rubbing is passed down from generation to generation and maintained because it is easy to do, safe, and considered to provide real benefits. The conclusion of this study confirms that red onion balur serves as a relevant family self-medication strategy. Recommendations for further research include the need for topical safety studies, clinical efficacy trials, and broader documentation of local practices to support the integration of traditional medicine with modern healthcare.